Comparative Analysis Assisted by Computational Fluid Dynamics (CFD) of the Economic and Simplified Boiling Water Reactor (ESBWR) Passive Cooling Systems Considering Nanofluids Addition - Gallardo Villarreal, José Manuel (My University, 2018)
ROM, CFD, Nanofluids, TRAC-U, ESBWR, Passive cooling systems
Keywords: ROM, CFD, Nanofluids, TRAC-U, ESBWR, Passive cooling systems